Metode Simple Multi Attribute Rating Technique Untuk Sistem Pendukung Keputusan Penentuan Penerima Beasiswa - Sri Surati; Sri Siswanti; Andriani Kusumaningrum (STMIK Sinar Nusantara, 2022)
Scholarships are a work program that exists in every public, private and madrasah school. The scholarship program is held to ease the burden on students in taking the study period, especially in terms of costs. The decision-making process is basically choosing the best alternative, such as structuring the problem, determining alternatives, determining possible values for alleatory variables, setting values, time preference requirements, and risk specifications. The purpose of this study is to find out how the Simple Multi Attribute Rating Technique method can be used in making decisions for determining scholarships. The results of functional testing found that the system has been running in accordance with the system design plan that has been made previously. The results of the system's feasibility testing with answers to questionnaires from respondents who have been carried out from the answers agree and strongly agree show the percentage of 94%.